Animated Interior - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (Interiority, 2021)
An animated interior represents a departure from the idea of interior space as a permanent and timeless entity. The understanding of animated characters in the interior allows for the emergence of our complex relationship with space through various forms of engagement. The understanding of an animated interior offers further possibilities that become the basis of design practice. This issue of the Interiority journal presents a collection of inquiries and approaches that reveal various animated qualities of the interior in various contexts. The articles address the character of the interior, which is dynamic and dependent upon various temporal conditions of inhabitation. At the same time, they demonstrate the possible design practices that could emerge from the understanding of animated interiors.